A NEW POSSIBLE INTERPRETATION OF DIGEST OF JUSTINIAN D.9.2.27.14: A CONTRIBUTION TO THE STUDY OF PRECURSORS OF ENVIRONMENTAL LAW IN ROMAN LAW - Aličić, Samir (Pravni zapisi, 2023)
The paper addresses the meaning of the Digest of Justinian 9.2.27.14, which deals with the case of damage caused by contamination of the soil by weeds. The author of this paper concludes that neither Celsus nor Ulpian had any doubt that in the case of the contamination of soil an interdictum quod vi aut clam could be brought, but only within a period of one year following the damage. This interdict is granted to either the owner, and, if the land was subject of the contract of lease, to the tenant (lessee), but only to one of them. Furthermore, an Aquilian action could also be brought, but only one of these two legal instruments could be used. The lawsuit could be brought both by the owner or by the tenant. The actio is granted to both the the owner and the lessee, not as an actio directa, but as an actio in factum ex lege Aquilia. The reason for this cannot be established with certainty.
Keywords: lex Aquilia; damnum iniuria datum; damage; extracontractual liability; interdictum quod vi aut clam; contamination; law of obligations; environmental law; Roman law